THE CARGO DISTRIBUTION IN THE PLANING PROCESS OF SCRAPER CONVEYOR - MAO Jun; WANG Xin; CHEN HongYue; ZHANG Yu (Jixie qiangdu)
In order to study the scraper conveyor load distribution in the process of cutting,a mathematical model between plow performance parameters and scraper conveyor transport performance parameters was established. Using numerical simulation obtained scraper conveyor loading capacity curve in condition of different planing speed ratio,different scraper conveyor lay length and different plow initial position,and analyzing its fluctuation characteristics. The results showed that: the maximum loading capacity of scraper conveyor is related to conveyor lay length,cutting speed ratio,plow face height,plow planing thickness,entity density of coal and so on,is independent of plow initial position; after reaching the maximum loading capacity of scraper conveyor,when planing ratio is odd,the loading capacity maintain maximum and constant,planing speed ratio to another value,the loading capacity presents fluctuation periodically.